Pengaruh Konseling Humanistik Terhadap Motivasi Belajar Siswa Kelas X di SMAN 1 Lingsar - I Made Gunawan (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
The objectives of this research are: to know how big influence on motivation to learn humanisticcounseling on subjects Biology class X grade students of SMAN 1 Lingsar, West Lombok in the academicyear 2016/2017. This type of research, experimental method with quantitative approach. The data collectiontechnique is a method of inquiry as the principal methods and methods of documentation, observation andinterviewing methods/ interview as a complementary method. The statistical analysis used in this research isusing t-test formula. Based on the discussion can be concluded that: there is the influence of humanisticcounseling on motivation to learn in the subjects of biology class X grade students of SMAN 1 Lingsar, WestLombok in the academic year 2016/2017. It can be seen from the results of the study are: t value of 4,131dan ttable value at significance level of 5% with N = 7, is greater than the value t table (4.131> 2.365) so that thereis a relationship that is